2019
DOI: 10.18203/2320-1770.ijrcog20191941
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance for Human Papilloma virus vaccines, experience at tertiary care centre of northern india: a hospital-based survey

Abstract: Background: Acceptance of HPV vaccine is varying widely worldwide in   range of 10-70%. For increasing the acceptability for HPV vaccine, finding the obstacles and catering them diligently is required. The aim of the study was to find out acceptability rate for HPV vaccine in northern India and various obstacles and facilitators affecting acceptance of HPV vaccine.Methods: A questionnaire based descriptive study was done in the Department of Obstetrics and Gynecology of King George Medical University, Lucknow,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…This may be one step in the right direction and also the need of the hour as one questionnaire based descriptive study has shown a very low acceptance rate (23%) of HPV vaccine in India. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be one step in the right direction and also the need of the hour as one questionnaire based descriptive study has shown a very low acceptance rate (23%) of HPV vaccine in India. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] In spite of this, a questionnaire based descriptive study has shown a very low acceptance rate (23%) of HPV vaccine in India, the root cause being lack of knowledge and high monetary cost of the vaccine. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%